Estudo ab initio do sistema molecular HCO de interesse atmosférico. - Coura, Daniel Vitor Barbosa (2018)
In this work high-level ab initio calculations have been performed using CASSCF determinants for a MRCI function and an ACV5Z-DK basis, jointly with a preliminary fit of a potential energy function to those points. Until the date of the defence of this dissertation it was possible to carry out a study of the global minimum of the potential energy surface of HCO, some local minimum and some transition states. The main objective of the work we have here started is the construction of a global potential energy surface for the ground state of the HCO molecule.